Ecological Crisis And Exploitation Of Women in Margaret Atwood’s Surfacing - Riyani Vadilla; Ferdinal Ferdinal; Silvia Rosa (Politeknik Negeri Padang, 2020)
The problem of ecological crisis and exploitation of women is a topic that is often discussed today because it occurs in various parts of the world. The natural conditions and fate of women both in developing and developed countries are in an alarming condition because the development and exploitation of nature causes water, soil and air pollution. Women who use nature for their daily needs with development are forced to become objects of capitalist patriarchal exploitation. In addition, the degradation of nature due to the interference of science and technology causes the degradation of natural ecosystems so that the survival of other living things such as plants and animals is disrupted. This descriptive study aims to examine the issue of ecological crisis and exploitation of women found in the novel Surfacing by Margaret Atwood by using the ecofeminism theory of Vandana Shiva and Maria Mies. This research uses 3 variables: 1. Reduction of women's uterus, 2. Development, 3. Exploitation . This research is a library research. To see the colors of representation, researchers used the theory of ecofeminism introduced by Vandana Shiva and Maria Mies. The results showed an ecological crisis and exploitation of women found in the novel Surfacing, namely (1) the reduction of the womb of women with the presence of modern science, (2) pornography of women and exploitation of animals for commercial purposes, (3) development and illegal logging for various interests industry